Human amniotic membrane application in oral surgery—An ex vivo pilot study - Odet, Stéphane; Solecki, Lauriana; Meyer, Christophe; Weber, Elise; Chatelain, Brice; Euvrard, Edouard; Barrabé, Aude; Gualdi, Thomas; Parmentier, Anne-Laure; Tatu, Laurent; Pouthier, Fabienne; Louvrier, Aurélien; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives The purpose of this pilot porcine study was to explore and illustrate the surgical application of human amniotic membrane (hAM) in an ex vivo model of medication-related osteonecrosis of the jaw (MRONJ). Material and methods Five oral and maxillofacial surgeons participated to this study. MRONJ was simulated on porcine mandible specimens. hAM was applied using four different techniques: implantation with complete coverage, implantation with partial coverage, apposition and covering graft material. At the same time, the surgeons evaluated how well the hAM handled and its physical properties during the surgery. Results Surgeons found that hAM had suitable mechanical properties, as it was easy to detach from the support, handle, bind to the defect and bury. hAM was also found to be strong and stable. The “implantation with complete coverage” and “implantation with partial coverage” techniques were the preferred choices for the MRONJ indication. Conclusions This study shows that hAM is a graft material with suitable properties for oral surgery. It is preferable to use it buried under the gingiva with sutures above it, which increases its stability. This technical note aims to educate surgeons and provide them with details about the handling of hAM in oral surgery. Clinical relevance Two surgical techniques for hAM application in MRONJ were identified and illustrated. hAM handling and physical properties during surgery were reported.